A Systematic Literature Review: Problem Solving Matematika Pada Kurikulum Matematika Di Amerika Serikat - Fauziah Putri; Iwan Junaedi; Mulyono (Universitas Insan Budi Utomo, 2024)
Problem solving is one of the skills that plays an important role in mathematics learning. Problem solving is at the core of mathematics education in the United States. The mathematics curriculum in the US emphasizes the development of students' abilities to understand concepts and apply them to solve problems in various contexts. This approach is reflected in various educational standards and initiatives, which aim to prepare students to face the challenges of the 21st century. This research aims to describe Problem Solving in the mathematics curriculum in the United States. The research method used is a Systematic Literature Review (SLR).The research findings indicate that (1) the standard education curriculum in the United States refers to the Common Core State Standards for Mathematics (CCSSM), which outlines what students should learn in mathematics from kindergarten through 12th grade (K-12). (2) Efforts have been made in the United States to improve students' problem-solving abilities, including an emphasis on Mathematical Practices, the implementation of PBL and inquiry-based learning, technology integration, process-focused assessments, and teacher professional development. Common Core State Standards for Mathematics emphasize conceptual understanding, Mathematical Practices, and problem-solving in real-world contexts, which have the potential to enhance students'.